The Eyewitness visual dictionary of cars. (New York : Dorling Kindersley ; Boston, Mass. : Distributed by Houghton Mifflin, 1992)
Text and labeled illustrations depict a variety of historical, classic, and contemporary automobiles and their components.
Includes index.
Keywords: Automobiles; Automobiles -- Pictorial works